Sharbat Ahmad Shahi: A Potent Unani Formulation for Mood Disorders - Khan, Afshan; Siddiqui, Aisha; Jafri, M.A; Asif, Mohd (International Journal of Scientific Research in Biological Sciences, 2018)
Mood disorders such as depression are the most ubiquitous disease amongst psychiatric disorders. According to the estimations of the World Health Organisation, depression will be the second leading cause of disability in 2020. Psychiatric disorders are the foremost problems in the world since relic. In Unani system of medicine, there is no any direct description of depression but it is described in detail under the heading of “Amraze nafsaniya”. This system has a gem of valuable single and compound formulations for psychiatric disorders as there are several mufrad (Single) drugs used to treat psychiatric disorders such as Aftimoon (Cuscuta reflexa), Badranjboya (Nepeta hindostana), Nilofar (Nymphaea alba), Gule surkh (Rosa damascena), Bisfaij (Polypodium vulgare) etc. Sharbat Ahmad Shahi is one of the polyherbal Unani preparations and it has been conventionally used in Malankholia (Melancholia), Insanity, Mania and for saudavi amraaz. It has been reported for its antidepressant potential in recent years.